Determinant Factors of Technical-Tactical Combinations Frequency in standing position during Womens World Senior Championships 2009 - David Eduardo López González (Federación Extremeña de Balonmano; University of Extremadura, 2011)
Abstract  Objective. To classify the perfomance  of world class women wrestlers as the frequency and characteristics of their Technical-Tactical Combinations (TTC) with effectiveness in the standing position during the most important competition on the international calendar 2009. Methods.  In the TTC were characterized all standing position effectives by a sample of 70 wrestlers, occupants of the top 10 in each of the 7 weight categories convened. Descriptive variables were used 5 of effectiveness, technical group, and characteristics of its phases. Variables were obtained determining the effectiveness, measured the "success rate" achieved by each fighter, all through factor analysis. Later wrestlers were classified by cluster analysis by Ward's method. Results. The most important factor related to get a medal  was the execution of legs attacks of with several possible endings started with almost no contact with the opponent, followed by the use of low-risk attacks launched from a firm grip. The wrestlers opted mostly for defense and counter low risk. Most of the competitors who had good results using several and alternative projections also managed to end their attacks. Conclusions. Characterization Model used and the factors of effectiveness in the fight standing obtained provided detailed explanations of the performance characteristics of the best wrestlers in the Senior World Championships 2009. The design of this research can be applied year after year in both freestyle and women's. Key words: Technical - Tactical Combinations, Rules, Fighting Women, Factor Analysis and Effectiveness